(untitled) (Comprehensive Journal of Science, 2026)
This study aims to examine the impact of digital transformation on improving the performance of technical higher education institutions. The research focuses on three main dimensions of digital transformation: technology and infrastructure, faculty training, and digital culture. The study was conducted from the perspective of faculty members at the Higher Institute of Science and Technology in Raqdalin, the study adopted the descriptive analytical approach, and a questionnaire was used as the primary tool for data collection. The study population consisted of all faculty members at the institute, totaling 86 individuals. Due to the relatively small size of the population, a comprehensive survey was conducted, and 70 valid questionnaires were analyzed. The Statistical Package for the Social Sciences (SPSS) was used to analyze the data and test the study hypotheses. The findings revealed that the dimensions of digital transformation—technology and infrastructure, faculty training, and digital culture—are available at a high level within the institution. The results also indicated a statistically significant impact of digital culture on improving institutional performance, while technology, infrastructure, and faculty training showed no significant effect under the current conditions of the institution, The study recommends strengthening digital culture and enhancing digital transformation initiatives to support the development and improvement of performance in technical higher education institutions